Awareness and Utilization of Big Data Management System by Lecturers in Universities: A Survey of Universities in Nigeria - Eneh, Anthonia C.; Oviri, Beatrice Uchenna; Opara, Vincent C. (NIU Journal of Educational Research, 2024)
The research investigated awareness and utilization of big data management systems by lecturers in universities: a survey of universities in Nigeria.  Lecturers at four (5) public universities in Nigeria namely: University of Port Harcourt, Imo State University, University of Benin, Benin City, Kogi State University and University of Lagos made up the population. The information was gathered via an online questionnaire that was distributed to respondents. Out of the 162 online responses, only 148 were valid and used for the analysis. Frequency, simple percentages and Mean scores were used to analyze the data. Results of the analysis show that lecturers are not aware of big data management tools and they do not know how to use big data management system tools. The increase in the number of data and the wide spread of technology were the two factors that contributed to the adoption of big data management systems. The study suggested, among other things, that information technology leaders of universities ideally demonstrate the importance and use of Big Data management system in their information technology strategic plans in order to address the need for big data management skills among lecturers in universities in Nigeria. Keywords: Big Data, Big Data Management System, University Lecturers, Information and Communication Technology Skills